Medullary Noradrenergic Neurons Mediate Hemodynamic Responses to Osmotic and Volume Challenges - Marques, Stefanne Madalena; Naves, Lara Marques; Silva, Talita de Melo e; Cavalcante, Keilah Valéria Naves; Alves, Juliana Milan; Ferreira-Neto, Marcos Luiz; de Castro, Carlos Henrique; Freiria-Oliveira, Andre Henrique; Fajemiroye, James Oluwagbamigbe; Gomes, Rodrigo Mello; Colombari, Eduardo; Xavier, Carlos Henrique; et al. (Frontiers in Physiology, 2021)
Despite being involved in homeostatic control and hydro-electrolyte balance, the contribution of medullary (A1 and A2) noradrenergic neurons to the hypertonic saline infusion (HSI)-induced cardiovascular response after hypotensive hemorrhage (HH), remains to be clarified. Hence, the present study sought to determine the role of noradrenergic neurons in HSI-induced hemodynamic recovery in male Wistar rats (290-320g) with hypotensive hemorrhage (HH). Medullary catecholaminergic neurons were lesioned by nanoinjection of antidopamine-β-hydroxylase–saporin (0.105 ng∙nl-1) into A1, A2 or both A1/A2 (LES A1; LES A2; or LES A1+A2, respectively). Sham rats received nanoinjections of free saporin in the same regions (SHAM A1; SHAM A2; or SHAM A1+A2, respectively). After 15 days, rats were anesthetized and instrumented for cardiovascular recordings. Following 10 min of stabilization, HH was performed by withdrawing arterial blood until mean arterial pressure reaches 60 mmHg. Subsequently, HSI was performed (NaCl 3 M; 1.8 ml∙kg-1, i.v.). The HH procedure caused hypotension, bradycardia and reduced renal, aortic, and hindlimb blood flows (RBF, ABF and HBF). The HSI restored mean arterial pressure (MAP), heart rate (HR), and RBF to baseline values in sham, LES A1 and LES A2 groups. However, concomitant A1 and A2 lesions impaired this recovery, as demonstrated by the abolishment of MAP, RBF and ABF responses. Although lesioning of only a group of neurons (A1 or A2) was unable to prevent HSI-induced recovery of cardiovascular parameters after hemorrhage, lesions of both A1 and A2 made this response unfeasible. These findings show that together the A1 and A2 neurons are essential to HSI-induced cardiovascular recovery in hypovolemia. By implication, simultaneous A1 and A2 dysfunctions could impair the efficacy of HSI-induced recovery during hemorrhage.